Comment protéger la santé des travailleurs dans un système qui ne repose pas sur les notions d’aptitude et d’inaptitude ? - Robert Plante; Luc Bherer; Michel Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
In Québec, in occupational health, the public health approach has been favoured over the individual medical approach because it is consistent with the objectives of the law, namely this community taking charge of its problems, and the reduction and even elimination of risk factors. Individual medical activities are limited to cases where the relevance and effectiveness of preventive benefits have been demonstrated. Some evaluative studies have shown that this Québec public health program approach works well in general, and is effective. Compared with the medical examination of each subject, it has a better potential for focusing energies on occupational exposures and on work organizational factors that could cause problems. Despite all its advantages, the Québec occupational health system is facing serious institutional and political resistance that has compromised its development and is gradually leading it to its dysfunction.